Managing Operational Risk Practical Strategies to Identify and Mitigate Operational Risk within Financial Institutions - Robertson, Douglas; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Operational risk is the risk of loss from inadequate or failed internal processes, people, and systems or from external events. This book explores the different types of operational risk that threaten financial institutions, and focuses on practical due-diligence methodologies that can be used to identify these risks before it is too late.
Keywords: Business; Accounting; Bookkeeping; Leadership; Finance; Risk management; Economic theory; Macroeconomics; Business and Management; Accounting/Auditing.; Finance, general; Risk Management; Business Strategy/Leadership.; Economic Theory/Quantitative Economics/Mathematical Methods; Macroeconomics/Monetary Economics//Financial Economics; Electronic books